The Synthesis of CH₃NH₃PbI₃₋ₓBrₓ under Uncontrolled Humidity for Perovskite Solar Cell Application - Kusumawardani, Cahyorini; Ikhsan, Jaslin; Budiasih, Kun Sri; Herlambang Nugroho; Widowati, Asri (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
CH₃NH₃PbI₃₋ₓBrₓ perovskite films were successfully synthesized under uncontrolled humidity using a two-step spin-coating method followed by Ostwald ripening (OR) treatment. Bromide incorporation into CH₃NH₃PbI₃ was achieved by diluting the pre-formed CH₃NH₃PbI₃ films with CH₃NH₃Br (MABr) solutions at various concentrations. X-ray diffraction (XRD) analysis confirmed the formation of a tetragonal perovskite phase with reduced lattice parameters as the bromide concentration increased, indicating successful substitution of I⁻ by Br⁻ ions. Scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX) characterization showed that moderate bromide incorporation (30–40 mg/mL) produced dense and uniform grains with homogeneous halide distribution, whereas excessive MABr resulted in non-uniform morphology and halide segregation, particularly under humid conditions. Optical analysis revealed a gradual blue shift of the absorption edge, consistent with band gap widening due to lattice contraction. Photovoltaic performance measurements demonstrated that higher MABr concentrations led to decreased current density and fill factor, attributed to excessive bromide content and defect formation. These findings indicate that controlled bromide incorporation via Ostwald ripening using an MABr concentration of 20 mg/mL effectively enhances the structural quality, film stability, and photovoltaic performance of CH₃NH₃PbI₃₋ₓBrₓ perovskite solar cells under humid environments.